Comparative Analysis of the Covid-19 Policy of Indonesia and Vietnam in 2020 - Hapsari, Renitha Dwi; Nugraha, Erwin Cahya; Putra, Bima Hermawan (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2021)
A virus started to spread in China by the end of 2019. Soon after, the world faces a global pandemic known as the Covid-19. The deadly and highly contagious virus threatens not only health security but also various socialeconomic aspects. In the chaotic world, the advancement of transportation technology contributes to the accelerated spread of the Covid-19 virus. The global movement of people becomes the biggest challenge for the national government to tackle during the global pandemic. Countries take different policies and measures to mitigate the spread of the virus. This paper conducts comparative policy analysis on two cases: Vietnam and Indonesia. The paper argues that the Vietnamese government tackles the virus mitigation more efficiently than the Indonesian government despite Vietnam's close geographical location to China. The Indonesian government is also relatively slower than the Vietnamese government concerning the policy responses.